Instrumental software package for simulation modeling of membrane separation processes of liquid dispersed systems - Pashchenko, Bogdan; Litvinenko, Alexander (Transfer of innovative technologies, 2021)
One of the main problems of socio-economic development of modern society in the XXI century is to improve the structure of the food industry as one of the leading links in the world economy. To achieve this goal, it is necessary to ensure the solution of a range of scientific, technical, economic and environmental issues, which requires a comprehensive combination of several modern technologies. A special place among them is occupied by membranes, which are used for separation of dispersed systems at many food enterprises and allow to create energetically and ecologically rational options for separation and concentration of solutions using a wide range of filter elements based on inorganic materials. Computer modeling plays an important role in their research. The current technical level of software allows to solve this problem, but only in the presence of a comprehensive research methodology based on information technology design. This will ensure the fullest consideration of all aspects of the technological process.